Upaya peningkatan pembelajaran bela diri pencak silat melalui pendekatan TARL (Teaching at The Right Level) pada Kelas XI-2 SMA Negeri 10 Semarang - Khasanah, Khikmahtul Khasanah (Motion: Journal Research of Physical Education, 2024)
This research aims to improve pencak silat learning abilities through a group work approach in class XI 2 SMA N 10 Semarang. The method used is classroom action research (PTK) with a quantitative approach. The research was carried out in two cycles, each cycle consisting of two meetings. The research results show that learning pencak silat using the Teaching at the Right Level (TARL) approach can improve student learning outcomes. Data on the completeness of student learning outcomes in the pre-cycle, after cycle 1, and after cycle 2 showed a significant increase. Thus, the TARL method is effective in improving the ability of class XI 2 students at SMA N 10 Semarang in learning pencak silat.